To solve the equation \( (13x - 2)(x - 34) = 0 \), we can use something called the zero product property. This means if you multiply two things together and get zero, then at least one of those things must be zero.
So, we set each part (or "factor") equal to zero:
- \( 13x - 2 = 0 \)
- \( x - 34 = 0 \)
Now, let’s solve each one!
For the first part:
\[ 13x - 2 = 0 \]
To get rid of the -2, we add 2 to both sides:
\[ 13x = 2 \]
Next, we need to get \( x \) by itself. Since \( x \) is being multiplied by 13, we divide by 13:
\[ x = \frac{2}{13} \]
For the second part:
\[ x - 34 = 0 \]
Here, we just add 34 to both sides to solve for \( x \):
\[ x = 34 \]
So, the answers to the equation \( (13x - 2)(x - 34) = 0 \) are:
\[ x = \frac{2}{13} \quad \text{and} \quad x = 34 \]
That’s it! We found both solutions!